A Multidisciplinary Approach to Capability in Age and Ageing - Falk Erhag, Hanna; Lagerlöf Nilsson, Ulrika; Rydberg Sterner, Therese; Skoog, Ingmar (International Perspectives on Aging, 2022)
This open access book provides insight on how to interpret capability in ageing - one's individual ability to perform actions in order to reach goals one has reason to value - from a multidisciplinary approach. With for the first time in history there being more people in the world aged 60 years and over than there are children below the age of 5, the book describes this demographic trends as well as the large global challenges and important societal implications this will have such as a worldwide increase in the number of persons affected with dementia, and in the ratio of retired persons to those still in the labor market. Through contributions from many different research areas, it discussed how capability depends on interactions between the individual (e.g. health, genetics, personality, intellectual capacity), environment (e.g. family, friends, home, work place), and society (e.g. political decisions, ageism, historical period). The final chapter summarizes the differences and similarities in these contributions. As such this book provides an interesting read for students, teachers and researchers at different levels and from different fields interested in capability and multidisciplinary research.